Determinan Perilaku Penyalahgunaan Napza Teori Health Belief Model : Studi Literatur 2015-2025 - Amanda Kartika Azzahra; Luqman Effendi (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Drug abuse is a serious global public health problem, with the prevalence in Indonesia reaching 1.73% or about 3.33 million people in 2023, mainly among those aged 15–24 years. Understanding the psychological determinants of this behavior is crucial to enhance prevention and rehabilitation efforts. Objective: To analyze determinants of drug abuse behavior based on the Health Belief Model (HBM) through a literature review of studies published between 2015 and 2025. Methods: A literature review of 8 academic articles from Google Scholar and PubMed, limited to open‑access Indonesian- and English‑language journals examining HBM constructs related to drug abuse and rehabilitation participation. Results: HBM variables were generally associated with drug abuse behavior and rehabilitation adherence, with self‑efficacy emerging as the most consistent determinant, followed by perceived susceptibility and perceived severity. Perceived barriers, especially complex administrative procedures, distance, costs, and stigma, were identified as major obstacles to engaging in rehabilitation. Conclusion: The HBM is useful for mapping determinants of drug abuse behavior and highlights the need to strengthen self‑efficacy, risk perceptions, and barrier reduction within health promotion and community‑based rehabilitation programs.